UNVEILING THE INVESTORS MIND: AN ANALYSIS OF BEHAVIORAL BIASES IN STOCK INVESTMENTS ACROSS AGE, SEX, INCOME, EXPERIENCE, EDUCATION, AND MARITAL STATUS - Antonius, Joscelyn; Dananjaya, Yanuar (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research examines how investor personal characteristics namely age, gender, income, education level, stock investing experience, and marital status are related to investor propensity to experience behavioral biases. Four types of behavioral bias investigated in this research are overconfidence, herding behavior, disposition effect, and sentiment bias. The object of the research is active Indonesian stock investors with minimal 1 year experience. It is found that female investors are more prone to herding behavior compared to male. Longer investing experience is related to lower disposition bias, but higher overconfidence. No other association between other personal characteristics and those four behavioral biases.